AKIBAT HUKUM DISPENSASI PERKAWINAN ANAK DI BAWAH UMUR - Kiki Amaliah; Zico Junius Fernando (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: This study uses a normative juridical legal research method, which is a problem approach by examining and reviewing a valid and competent statutory regulation to be used as a basis for problem solving. The steps in this research use juridical logic. Primary legal materials consist of statutory regulations, official records or minutes in making laws. Secondary legal materials are the work of legal experts, internet sites and other reading books related to the research title. The analysis of the legal materials mentioned above uses a normative analysis method, starting with grouping the same legal materials and information according to sub-aspects and then analyzing and interpreting all aspects to understand and provide a complete picture of the results. This study discusses the consequences of dispensation for underage marriage. The legal consequences that arise if the application for dispensation is accepted by the Religious Court or District Court, namely obtaining the right to be able to carry out marriages and the marriage is legally and stately legal. If rejected, they may re-apply and the last resort is to file an appeal to the Supreme Court. In addition, judges of the Religious Courts and District Courts must be more selective in determining the application for dispensation for the age of marriage, so as to reduce the level of underage marriage that occurs in society.Keywords: Marriage Dispensation, Underage Marriage, Due to Child Marriage